2019
DOI: 10.3762/bxiv.2019.16.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fabrication and characterization of Si1-xGex nanocrystals in as-grown and annealed structures: A comparative study

Abstract: Multilayer structure comprising of SiO2/SiGe/SiO2 were obtained by depositing SiO2 layers using reactive direct current magnetron sputtering (dcMS), whereas, Si and Ge were co-sputtered using dcMS and high impulse power magnetron sputtering (HiPIMS), respectively. The as-grown structures subsequently underwent rapid thermal annealing (550 – 900 °C for 1 min) in N2 ambient atmosphere. The structures were investigated using X-ray diffraction, high-resolution transmission electron microscopy along with photocondu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…Additionally, TiO2 tends to increase diffusion barrier for Ge compared to Ta2O5, where the XRD-peak is closer to standard Si position. It is noteworthy to mention here that having rutile-TiO2 can further enhance the PLcharacteristic as has been discussed in earlier studies [5].…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Additionally, TiO2 tends to increase diffusion barrier for Ge compared to Ta2O5, where the XRD-peak is closer to standard Si position. It is noteworthy to mention here that having rutile-TiO2 can further enhance the PLcharacteristic as has been discussed in earlier studies [5].…”
Section: Resultssupporting
confidence: 56%
“…The photoluminescence obtained from SiGe NPs in oxides are dominated by; defectrelated emission in the UV-regime, band-toband transition, localized states within the oxide (i.e., oxygen vacancies), NPs posing quantum confinement effect and the interface between the NPs and the oxide matrix [5,10]. However in this current study the origin of the observed PL peaks is not discussed.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation